2017
DOI: 10.1016/j.stemcr.2017.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Human Pancreatic Endoderm Cells Reverses Diabetes Post Transplantation in a Prevascularized Subcutaneous Site

Abstract: SummaryBeta-cell replacement therapy is an effective means to restore glucose homeostasis in select humans with autoimmune diabetes. The scarcity of “healthy” human donor pancreata restricts the broader application of this effective curative therapy. “β-Like” cells derived from human embryonic stem cells (hESC), with the capacity to secrete insulin in a glucose-regulated manner, have been developed in vitro, with limitless capacity for expansion. Here we report long-term diabetes correction in mice transplante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 34 publications
(93 reference statements)
4
62
1
Order By: Relevance
“…Implants of device‐encapsulated hiPS‐PE in a preformed pouch reduced the number of recipients with low β‐cell mass at PT‐week 20. Pepper et al showed that such site pretreatment facilitates survival and function of nonencapsulated pancreatic islet cells under the skin of mice, possibly by prevascularizing their microenvironment ; they also found it to support development of in vivo β‐cell functions in nonencapsulated hES‐PE implants, but also of large cysts lined by PE‐generated epithelial cells . In implants with metabolic control at PT‐week 20, we only noticed small cell lined cavities in the devices, with endocrine cells composing the major tissue fraction.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Implants of device‐encapsulated hiPS‐PE in a preformed pouch reduced the number of recipients with low β‐cell mass at PT‐week 20. Pepper et al showed that such site pretreatment facilitates survival and function of nonencapsulated pancreatic islet cells under the skin of mice, possibly by prevascularizing their microenvironment ; they also found it to support development of in vivo β‐cell functions in nonencapsulated hES‐PE implants, but also of large cysts lined by PE‐generated epithelial cells . In implants with metabolic control at PT‐week 20, we only noticed small cell lined cavities in the devices, with endocrine cells composing the major tissue fraction.…”
Section: Discussionmentioning
confidence: 54%
“…The significance of this in vivo marker was evaluated by its correlation with glucose control and with the β‐cell mass as measured in situ on intact implants, a more precise method than previous measurements on retrieved and dispersed implants. The first modification consisted in increasing the number of cells in the device at start, the second in implanting the device in a preformed pouch, a method that was reported to improve outcome of nonencapsulated islet cell and hES‐PE implants .…”
Section: Introductionmentioning
confidence: 99%
“…3,4 These oscillations are highly synchronized, due to gap junction (GJ) coupling between β-cells. 5-7 The nature of these oscillations depends on the proliferative, 8 developmental 9,10 and differentiated 11,12 state of the cell. Multiple animal models of diabetes have also demonstrated that the impaired insulin secretion characteristic of this disease, is due, in part, to dysfunctional Ca 2+ oscillations, 13-18 with studies on human β-cells corroborating this finding.…”
Section: Introductionmentioning
confidence: 99%
“…Some strategies have been used to overcome these limitations, including encapsulation, scaffolds, accessory cells, and/or trophic factors such as fibroblast growth factor (aFGF and bFGF) or vascular endothelial growth factor (VEGF) plus hepatocyte growth factor (HGF; Golocheikine et al, 2010;Kawakami et al, 2000;Kawakami et al, 2001;Sakata et al, 2014;Smink et al, 2017). In the last year, a few studies of subcutaneous islet transplantation have been published, highlighting the great interest of the scientific community in using this anatomical site (Bertuzzi & De Carlis, 2018;Farina et al, 2017;Hsu, Fu, & Wang, 2017;Komatsu et al, 2017;Pathak et al, 2017;Pepper et al, 2017;Perez-Basterrechea et al, 2017;Uematsu et al, 2018;Vlahos, Cober, & Sefton, 2017). However, there have been few attempts to apply this approach in humans.…”
Section: (D)mentioning
confidence: 99%